From a Reservoir Building to the Main Library of the Universitat Pompeu Fabra - Magre, Anna (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
The lecture deals with the challenge of converting a reservoir building dating from the nineteenth century into the main library of the Universitat Pompeu Fabra, and of maintaining an equilibrium between the functional requirements of a modern university library and the architectural and historical features of the building.